Perioperative Complications and Early Clinical Outcomes Following ACL Reconstruction with Soft Tissue Quadriceps Tendon Autograft in Adolescent Athletes. Issue 7 (30th July 2021) - Jasty, Naveen; Cook, Danielle; Liotta, Elizabeth; Heyworth, Benton
Objectives: Quadriceps tendon (QT) autograft has emerged as an increasingly popular soft tissue graft alternative to the hamstring tendon (HS) autograph for ACL reconstruction (ACLR). However, utilization of the technique is not yet widespread, particularly in the population of adolescent athletes, for whom safety and effectiveness of the technique remains under-investigated, despite this being the most affected epidemiologic sub-population, with regard to primary ACL injury, post-ACLR re-tear, and overall complications. The study hypothesis was that QT-ACLR would have equivalent or lower rates of perioperative complications and early ACL re-tear than historically reported for HS ACLR. Methods: A retrospective review of all 12-19 year-old athletes who underwent primary QT-ACLR by a single surgeon at a tertiary care pediatric hospital were included, with prospective outreach performed at 1 and 2 years to collect PROs and confirm absence of ACL re-tear or revision surgery. Patients with <6 months follow-up were excluded to insure adequate reporting of early perioperative complications. Patients with between 6-12 month follow up were excluded from the ACL re-tear analysis. Concomitant procedures at the time of primary ACL surgery, perioperative and early post-operative complications, and subsequent surgeries were analyzed. A sub-analysis excluding the first 25 knees was performed to eliminate any potential effects of a surgical 'learning curve'. Results: 90 patients (93 knees, 70% female) were included, with a mean age of 16.0 years (±1.85) and mean follow up of 12.6 months (IQR 9.1-21.4). Concomitant meniscal pathology was detected in more than half of patients, with 30% undergoing meniscal repair and 27% partial meniscectomy. There were 51 complications overall in 36 knees (39%, Table 1). Secondary surgery for a complication was performed in 22 knees (24%), most commonly for a cyclops lesion/arthrofibrosis (15%), but also for revision ACLR (5%) and removal of implants (1%). Of note, 6 additional knees (6%) were diagnosed by MRI for a cyclops lesion/arthrofibrosis, but were successfully treated with non-operative measures, including physical therapy, dynamic splinting, and/or intra-articular cortisone injections. ACL graft tear was more common in the first 25 knees for whom QT-ACLR was performed (16% vs. 1%, p=0.02), indicating that initial re-tear could be a function of the surgical learning curve and technique adjustments. Early graft tear rate of 5% is similar to reported rates in HS autograft in adolescents. Arthrosibrosis/cyclops lesions were more frequently observed than historically reported for other graft types, and were not significantly different based on learning curve (20% vs. 22%, p=1.00). Pedi-IKDC (Table 2) showed significant improvement from baseline to 6-month (p<0.001) and 1-year time (p<0.001) period. Patients without complications had a significantly higher Pedi-IKDC score at 1 year follow up (mean, 93.9) compared to those with complications (mean, 85.5; p=0.04). Conclusions: Quad tendon ACLR shows a relatively high overall early post-operative complication and subsequent surgery rate in adolescents, most notably cyclops lesions/arthrofibrosis, most cases of which underwent arthroscopic debridement/LOA. This is consistent with previous adult QT-ACLR studies. Graft tear rates at 1-year post-operatively are similar to historically reported re-tear rates of the HS ACLR for adolescents, with a higher re-tear rate in the earlier sub-cohort, which may relate to surgical learning curve. Continued research into minimizing risks and quantifying longer term ACL re-tear risk will be critical for this young, active population, who are increasingly undergoing ACLR with the QT autograft, which remains relatively understudied, particularly in the adolescent sub-population.